The Kantian theory of autonomy from Islamic perspective and its theoretical consequences in Islamic Moral Education / Javad Fakhkhar Toosi - Javad Fakhkhar , Toosi (2019)
This research discusses the acceptance of the Kantian theory of autonomy in Islam and its implication on the objectives and methods of Islamic moral education. Most Muslim scholars have opposed Kantian theory, while those who support it do so from the almu 'tazilah interpretation of Islam. The purpose of this study is to identify what the viewpoint of Islam is about this theory and what changes in the objectives and methods of Islamic moral education will occur based on the theory. The importance of this research is that modern education is based on rationality and freedom. These are embodied in autonomy which introduces the highest level of rationality and freedom and Islamic education should reveal its position on these two. The Islamic perspective of this issue outlines its policy on Islamic moral education. To achieve the purpose of the current study, a qualitative method has been used. A critical analysis is performed to respond to autonomy's objections from the Islamic point of view, as well as the inference method for gaining an Islam's view about this theory. The first achievement of this study is that, from the al- 'As 'ar"iyya viewpoint, autonomy is compatible with Islam and in such a way the path is not limited to the al-mu 'tazilah viewpoint. In addition, this result which is a very novel and unprecedented result shows that based on all theological schools, the autonomy is consistent with Islamic teachings. We also find that, Islam has accepted freedom of will from external motives as it has been raised in the theory of autonomy. The second and third achievements of the present research are that, the admission of autonomy leads to influence on the sub-objectives and some methods of Islamic moral education. The current research concludes that, the study of autonomy from the Islamic perspective is indispensable for Muslim thinkers.